Plastic deformation mechanisms of FeSiCrNi high silicon steel based on local canning compression - Hao Feng; Tao Wang; Jianchao Han; Shuyong Jiang; Bingyao Yan; Dong Sun; Peng Lin; Liping Bian; Junbo Yu; Yanqiu Zhang (Journal of Materials Research and Technology, 2024)
High silicon steel has excellent soft magnetic properties, but a poor plasticity limits its practical application seriously. In this research, a novel FeSiCrNi alloy short for Fe-6.5Si–2Cr–12Ni (wt%) was designed and deformed via the local canning compression process at room temperature. It was shown that the FeSiCrNi alloy presents a relatively high plasticity in a triaxial compressive stress state. Geometrically necessary dislocations ensure the compatibility of plastic deformation for FeSiCrNi alloy. There are a small number of η and γ textures inside the FeSiCrNi sample. The intensity of η texture nearly keeps steady, while the intensity of γ texture increases slightly with the level of plastic deformation increasing. Additionally, the intensity of {112}<111> copper texture increases with the increase of plastic deformation. Lath structures dominate the inhomogeneous plastic deformation of FeSiCrNi alloy and then integrate with the phase α-Fe. The main deformation mechanism of FeSiCrNi alloy is dislocation slip rather than twinning which has not been observed yet. The order degree of FeSiCrNi alloy continuously decreases, and deformation bands, dislocation walls and dislocation cells are successively formed, as the compression proceeds. It is feasible to produce FeSiCrNi components in cold forming process.